The impact of empathy on professional identity among Chinese junior male nurses: a moderated mediation model - Hezi Mu; Hezi Mu; Yi Cui; Lihua Zhang; Qin Liu; Lanfang Zhang; Haoshuang Yang; Changchang Chen; Na Liu; Yinling Zhang (Frontiers in Psychology)
BackgroundNursing care is essential, but the role of junior male nurses in medical and health services is underestimated; thus, many junior male nurses leave the profession due to a lack of professional identity.ObjectiveThis study examined how the mediating effect of emotional intelligence and the moderating role of locomotion mode influence the relationship between empathy and professional identity among Chinese junior male nurses.MethodsThis cross-sectional descriptive study was conducted among junior male nurses in China from December 2021 to May 2022. We asked participants from ten hospitals to complete a questionnaire regarding empathy, emotional intelligence, locomotion mode, and professional identity. Bootstrap and simple slope methods were used to test the moderated mediation model.ResultsEmotional intelligence partly mediated the effects of perspective-taking on professional identity (β = 0.253, p < 0.05). Furthermore, locomotion mode moderated the relationships between perspective-taking and emotional intelligence, perspective-taking and professional identity, and emotional intelligence and professional identity (β = 0.136, p < 0.01; β = 0.107, p < 0.05; β = −0.155, p < 0.01).ConclusionThe findings revealed that,the mediating effect of emotional intelligence on the relation between perspective-taking and professional adaptability was moderated by locomotion mode. Whereas. These findings are meaningful for early intervention and the improvement of professional identity among junior male nurses.